Pengembangan Sistem Digital Image Colorimetry (DIC) Untuk Pemantauan Polutan Nitrogen Di Perairan - Mulia Ramadhani, Adella; Dono Wilopo, Mukti; Johan, Yar; Iresta Wardani, Firdha; Firdaus, M. Lutfi (PendIPA Journal of Science Education, 2025)
The presence of ammonia in waters needs to be monitored because of its toxic nature, especially in the form of free ammonia (NH₃). High concentrations of free ammonia can disrupt the balance of aquatic ecosystems, reduce dissolved oxygen levels, inhibit the growth of aquatic organisms, and even cause mass mortality in fish and other biota. The purpose of this study is to build the Digital Image Colorimetry system for detecting ammonia and assess the accuracy of the DIC method compared to the well-known established spectrophotometric method. Analysis from 5 locations of saline water, salinity and pH levels were still within normal limits, ranging from 33-34 ppt for salinity, while pH is 7.5-7.9. The ammonia content at the sampling point was still considered safe, in accordance with the quality standard (0.3 ppm). The results of ammonia concentration measurements using the DIC method and the spectrophotometric method show a neglegible level of difference and have an accuracy value above 90%. These findings indicate that DIC can be used as an alternative method for measuring ammonia, especially for rapid analysis in the field.